Proyección de requerimientos en el sistema de gas para levantamiento artificial, entre los años 1977 – 1982 - Chávez Morán, Hugo Alejandro (1989)
Proyección de requerimientos en el sistema de gas para levantamiento artificial, entre los años 1977 – 1982